Electronic nicotine delivery systems (ECs) and COVID-19: the perfect storm for young consumers (2020)
The COVID-19 pandemic caused a change in our society and put health systems in crisis worldwide. Different risk factors and comorbidities have been found that increase the risk of mortality when acquiring this infection. The use of alternative devices to the cigarette like the electronic cigarettes, the vapers have been studied widely and generators of great controversy since it has been discovered that they also produce different pulmonary affections. When developing the SARS-CoV2 infection, different theories have been generated about the greater predisposition to a worse prognosis of people who use electronic cigarettes; however, the information on this continues in discovery. A group of experts made up of oncologists, infectologists, pulmonologists, and epidemiologists met to review the literature and then generate theories about the impact of electronic cigarettes on SARS-CoV2 infection.